Prescribing infant formula to allergic babies - M.J. Lombard; I. Labuschagne; E. van Niekerk (South African Family Practice, 2012)
Exclusive breastfeeding and postponement of complementary foods to four to six months of age are recommended for the prevention of food allergies. However, many infants receive formula milk for a number of reasons. Various types of formula are indicated to prevent or treat allergy and food intolerance.